Penguatan Peran Orang Tua melalui Aktivitas Kolaboratif dalam Pembuatan Mini Storybook - suci salsabila, dara; Arifani, Rania; Agustira, Dianika; Az Zahra, Aisya; Suaida; Sherly Utami, Winda; Indriyani (Jurnal Pengabdian Masyarakat Pinang Masak, 2025)
This community service activity at TK Negeri 31 Simpang Sungai Duren aimed to strengthen parental involvement in early childhood education through a collaborative mini storybook-making activity. The program was carried out in three stages: preparation, implementation, and evaluation. During the activity, children drew, colored, and narrated their personal experiences, while parents helped arrange the storyline and wrote simple narratives based on the children's explanations. Throughout the process, children showed high enthusiasm and active engagement in each step. The results indicated that the activity successfully enhanced children's storytelling skills, confidence, creativity, and emotional expression. Parents also demonstrated increased involvement and stronger emotional bonding with their children. Overall, this activity provided a meaningful learning experience and proved that creative literacy activities involving both parents and children can effectively support early childhood development and strengthen the role of families in education.